Innovation of the health monitoring system for pregnant and breastfeeding mothers through independent health applications as an effort to reduce stunting - Ngadiyono Ngadiyono; Suparmi Suparmi; Ulfah Musdalifah; Izzatul Arifah (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Failure to grow in children or what is often called stunting is one of the focuses of global problems, including Indonesia. Globally, stunting is one of the goals Sustainable Development Goals (SDGs). Stunting is a problem of chronic malnutrition caused by inadequate nutritional intake over a long period of time due to providing food that does not meet nutritional needs. Stunting can occur when the fetus is still in the womb and only appears when the child is two years old. Based on the results of the Indonesian Nutrition Status Survey (SSGI), the stunting prevalence rate in Indonesia fell from 24.4% in 2021 to 21.6% in 2022. This figure is still above the threshold set by the World Health Organization (WHO), namely 20%. The stunting prevalence rate in Demak Regency was ranked seventh highest in Central Java in 2019 at 50.23% and is one of 60 stunting districts. In 2019 in Demak Regency there were 4.25% or 6,129 toddlers out of a total of 97,212 toddlers who had the potential to experience stunting. This situation is a priority for the Demak Regency government to handle by determining 10 locations that will be prioritized in 2020 and 2021Purpose: To produce monitoring and promotion system application for pregnant and postpartum mothers as well as breastfeeding mothers including toddlers can detect early health problems for mothers and toddlers and is named the child stunting preventive application (ASTA).Method: This research uses research and development methods orResearch and Development (R&D). This research method is used to produce certain products and test the effectiveness of a product. This research was conducted in December 2022. The population of this study was pregnant women in Demak Regency with a sample of 24 people who were divided into two, namely 12 people as the intervention group and 12 people as the control group. The influencing variable in this study is ASTA and the influenced variable is health maintenance behavior during pregnancy, postpartum and toddlers. This research is divided into four stages, namely design, analysis, engineering and evaluation.Results: Based on the statistical test output, it is known that Asymp. Sig. (2-tailed) is worth 0.025. From this value it can be concluded that H0 rejected. This means that there are differences in the level of potential stunting in the control group respondents in terms of the pre-post treatment results. Meanwhile, it is known that in the intervention group the value of Asymp. Sig. (2-tailed) namely 0.157. This value is >0.05, so it can be concluded that H0 accepted. This means that there is no difference in the level of potential stunting between pre-post treatments in the intervention group given the ASTA application.Conclusion: There is no significant effect of using the ASTA application on the criteria for potential stunting and there is no significant difference in potential stunting data between the control and intervention groups, either before or after treatment. However, the stunting prevalence ratio is 0.7 (<1) indicating that the ASTA application is a factor that can reduce the potential for stunting.